Intrinsic Rate of Increase (rm) of Aphis Gossypii Glover Infesting Brinjal Plants (Journal of Bio-Science, 2011)
Context: Intrinsic rate of natural increase (rm) of Aphis gossypii is important factor to know the actual increase of population which is governed by physical factors of environment.Objectives: The aims of this study were to determine the intrinsic rate of natural increase (rm) of A. gossypii which is the basic knowledge of IPM program.Materials and Methods: The nymphal duration, pre-reproductive period, reproductive period, fecundity, longevity, etc. were observed within the glass chimneys. The newly born nymphs were considered as F1 generations. Similarly, the first progeny of F1 generation were released in other glass chimneys to have F2 generation. In this way, F3, F4 and F5 generations were obtained. Data for duration between birth of a nymph and its first laid progeny (d) and number of progeny (Md) per female were recorded. Altogether data of 8 replications were considered for the calculation of intrinsic rate of natural increase (rm) of A. gossypii infesting brinjal plants.Results: Intrinsic rate of natural increase (rm) value was highest (0.322 ± 0.005) for the F1 generation, followed by F2 (0.317 ± 0.003) and it was lowest (0.303 ± 0.002) for F5 generation. Temperature influenced the (rm) significantly (r= 0.903, p